2021
DOI: 10.2166/ws.2021.044
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on households’ water use in Uganda

Abstract: The unprecedented outbreak of COVID-19 necessitated the promotion of better hygiene practices to curb the spread of the virus. Better hygiene requires that households have a stable supply of water. However, little is known about the predictors of changes in water use in emergency situations such as COVID-19 in Uganda. This study uses data from a cross-sectional survey to examine the changes in the quantities of water used by 1639 Ugandan households due to COVID-19. This article also explores the factors that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This implies that water consumption increased after March 2020 because households probably adhered to COVID-19 health protocols, which required more water for personal hygiene. The results of this study bear semblance with the finding of Sempewo et al (2021) in Uganda, which indicates that the amount of water consumed by households increased due to improved hygiene practices. It must, however, be pointed out that access to clean and affordable water is not a problem that stemmed from the COVID-19 pandemic; rising water prices, shortages and dry taps among other water supply challenges were some of the issues earlier identified by Gondo and Kolawole (2020) prior to the pandemic.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This implies that water consumption increased after March 2020 because households probably adhered to COVID-19 health protocols, which required more water for personal hygiene. The results of this study bear semblance with the finding of Sempewo et al (2021) in Uganda, which indicates that the amount of water consumed by households increased due to improved hygiene practices. It must, however, be pointed out that access to clean and affordable water is not a problem that stemmed from the COVID-19 pandemic; rising water prices, shortages and dry taps among other water supply challenges were some of the issues earlier identified by Gondo and Kolawole (2020) prior to the pandemic.…”
Section: Resultssupporting
confidence: 82%
“…The outbreak of coronavirus disease (COVID-19) in late 2019 in Wuhan, China, and which has since become a pandemic calls for a behaviour change ( Sempewo et al, 2021 ). The most important hygiene practice in stemming the spread of COVID-19 is handwashing with soap and clean water.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural campaigns aimed at hygiene practices, like washing hands and wearing and washing facemasks, had stronger associations with water insecurities, as they increased needs for clean water in a context in which it may be seasonally in short supply, low in quality, or difficult to access in vulnerable communities. Studies in other low-and middle-income countries in other parts of the world have also found that risk-reducing practices require access to more clean water, and this may not be easily available (Sempewo et al, 2021;Stoler et al, 2021;Zvobgo & Do, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bich-Ngoc & Teller (2020) developed a model that showed that impact of dry weather has a much stronger impact on water demand in the Liège (Belgium) conurbation (up to a 19% surge for extreme dry weather) than a reduction in outbound tourism (increase of 2% to 5% under the most extreme reduction) due to pandemic measures. Finally, the only study conducted in a developing country showed that most Ugandan households had an increase in quantity of water utilised after March 2020, based on household survey data (Sempewo et al 2021).…”
Section: Existing Literaturementioning
confidence: 99%